Invivo and Invitro Acaricide Efficacy Evaluation on Cattle Ticks in Selected Areas of Wolaita and Dawuro Zones, Ethiopia (Global Journal of Science Frontier Research, 2015)
This study was conducted from June, 2013 to May, 2014 in selected areas of Wolaita and Dawuro zones, with the core intentions of to assess the type and efficacy of the most frequently used acaricides in the areas, to identify the most prevalent cattle tick species and recommend the effective acaricide for cattle tick control. To achieve these objectives preliminary survey; invitro and invivo acaricide efficacy evaluation techniques have been conducted. The major tick species identified in order of their importance were Rhip(Boophilus) decoloratus (60.92%), Amblyomma variegatum (28.26%), A. cohaerens (7.82%) and A. gemma (3.0%). Diazinon 60%EC, Amitraz 12.5%, Ivermectin and Deltamethrin, according to their importance, was the acaricides frequently used in the areas. For the invitro technique, a total of 320 Rhip(Booph) decoloratus and 320 A. variegatum engorged adult female ticks were collected from each study sites and the standard modified adult immersion test (AIT) was employed for two successive round. On the other side of study, the efficacies of all the four acaricides at dose of concentration recommended by the manufacturer were assessed all the way through purposively selecting a total of 255 naturally tick infested cattle aged between 1 to 5 years.
Keywords: acaricides; cattle; efficacy evaluation; invivo and invitro; ticks